2012
DOI: 10.1111/j.1574-6941.2012.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Modern stromatolite phototrophic communities: a comparative study of procaryote and eucaryote phototrophs using variable chlorophyll fluorescence

Abstract: Stromatolites are laminated organosedimentary structures formed by microbial communities, principally cyanobacteria although eucaryote phototrophs may also be involved in the construction of modern stromatolites. In this study, productivity and photophysiology of communities from stromatolites (laminated) and thrombolites (nonlaminated) were analysed using fluorescence imaging. Sub-samples of mats were excised at Highborne Cay, Bahamas, and cross-sectioned to simultaneously analyse surface, near-surface (1-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The result has been comparatively few studies portraying the ecological role of stromatolite communities in their modern environments. Perkins and colleagues () investigated this ecological dynamic in terms of the physiology of stromatolite algal communities. They, informatively, demonstrated that pioneer and successional cyanobacterial mat types had higher productivity than their intermediate mat communities, but still lower productivity than eukaryote‐dominated (diatoms, specifically) stromatolite mats (Perkins et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The result has been comparatively few studies portraying the ecological role of stromatolite communities in their modern environments. Perkins and colleagues () investigated this ecological dynamic in terms of the physiology of stromatolite algal communities. They, informatively, demonstrated that pioneer and successional cyanobacterial mat types had higher productivity than their intermediate mat communities, but still lower productivity than eukaryote‐dominated (diatoms, specifically) stromatolite mats (Perkins et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Perkins and colleagues () investigated this ecological dynamic in terms of the physiology of stromatolite algal communities. They, informatively, demonstrated that pioneer and successional cyanobacterial mat types had higher productivity than their intermediate mat communities, but still lower productivity than eukaryote‐dominated (diatoms, specifically) stromatolite mats (Perkins et al ., ). This suggests an important role for stromatolite communities in coastal systems, especially in terms of the productivity input from different algal groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparatively, microbial eukaryotes are less-well studied. Nonetheless, metabarcoding and imaging approaches suggest that they are moderately abundant and diverse in microbialites from Cuatro Ci enegas (Breitbart et al, 2009), lake Alchichica (Couradeau et al, 2011;Sagha€ ı et al, 2015), and several marine stromatolites (Al-Qassab et al, 2002;Perkins et al, 2012;Bernhard et al, 2013;Mobberley et al, 2013;Edgcomb et al, 2014). Metagenomics can, via the direct sequencing of environmental DNA, inform about the metabolic potential of natural communities (Tringe and Rubin, 2005;Dinsdale et al, 2008).…”
Section: Introductionmentioning
confidence: 99%